Concept of Simple Proof of Bankruptcy and PKPU Cases for Apartment and Flat Developers Based on SEMA Number 3 of 2023 - Putra Adibil Anam (Faculty of Law, Universitas Pekalongan, 2022)
This study aims to determine the formulation of SEMA 3/2023 which states that apartment and flat developers cannot be declared bankrupt because they do not meet the simple evidentiary elements regulated in Article 8 paragraph (4) of the Kepailitan dan PKPU, and how it impacts justice and legal certainty for consumers who act as concurrent creditors. The formulation of the problem is how is the concept of a bankruptcy petition against apartment developers who do not meet the simple evidentiary requirements based on SEMA 3/2023? and, what are the implications for justice and legal certainty for creditors (consumers) if there are limitations on simple evidentiary requirements in SEMA 3/2023? This type of research is normative law with a statutory regulatory approach method. The results of this study are, first, SEMA 3/2023 emphasizes that a bankruptcy petition against apartment and flat developers does not meet the simple evidentiary elements because in practice it is not clear about the type of debt in the case. Second, with the existence of SEMA 3/2023, it is actually a legal breakthrough to guarantee justice and legal certainty for consumers who occupy concurrent creditors. This is considered because consumers are often harmed when developers experience financial difficulties or fail to fulfill their obligations. With the existence of SEMA 3/2023, it can be ensured that consumer interests remain protected.